2004
DOI: 10.1002/ajmg.a.30189
|View full text |Cite
|
Sign up to set email alerts
|

Costello syndrome with growth hormone deficiency and hypoglycemia: A new report and review of the endocrine associations

Abstract: We describe an 18-month-old boy with Costello syndrome (CS) with proven partial growth hormone (GH) deficiency and hypoglycemic episodes. The hypoglycemia is deemed to be due to cortisol deficiency. This report represents the second published case of cortisol deficiency in the CS. A brief review of the endocrine disturbances in the syndrome is provided. We highlight the need for careful endocrinological evaluation of individuals with CS. ß 2004 Wiley-Liss, Inc.KEY WORDS: Costello syndrome; growth hormone; cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 11 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…46 Hypoglycemic episodes unresponsive to GH therapy responded well to cortisone replacement in another individual. 47 Thus, cortisol deficiency may also be considered. Because of the severe feeding difficulties, most loose joints, particularly the fingers.…”
Section: Treatment Of Manifestationsmentioning
confidence: 99%
“…46 Hypoglycemic episodes unresponsive to GH therapy responded well to cortisone replacement in another individual. 47 Thus, cortisol deficiency may also be considered. Because of the severe feeding difficulties, most loose joints, particularly the fingers.…”
Section: Treatment Of Manifestationsmentioning
confidence: 99%
“… 1 Costello et al ., 1977 and Costello et al ., 1996; Der Kaloustian et al ., 1991; Martin and Jones, 1991; Borochowitz et al ., 1992; Teebi et al ., 1993; DiRocco et al ., 1993; Izumikawa et al .,1993; Kondo et al .,1993; Patton et al ., 1993; Phillip and Mancini, 1993; Zampino et al ., 1993; Say et al ., 1993; Yoshida et al ., 1993; Davies et al ., 1994; Okamoto et al ., 1994; Fryns et al ., 1994; Torres et al, 1994; Umans et al ., 1994; Torrelo et al, 1995; Mori et al ., 1996; Fukao et al ., 1996; Johnson et al ., 1998; Pratesi et al ., 1998; Tomita et al, 1998; Siwik et al ., 1998; Franceshini et al, 1999; Szalai et al , 1999; van Eeghen et al, 1999; Bisogno et al ., 1999; Innes and Chudley, 2000; Moroni et al ., 2000; Sigaudy et al ., 2000; Hatamochi et al ., 2000; Boente et al, 2001; Gripp et al, 2002; Kaji et al ., 2002; Kamoda et al ., 2002; van den Bosch et al ., 2002; Urakami et al ., 2002; Kawame et al, 2003; Delrue et al, 2003; Mancini et al ., 2003; DiRocco et al ., 2003; Nasca et al, 2003; Cakir et al ., 2004; Waldburg et al ., 2004; Dickson et al, 2004; Gregersen et al ., 2004; Stein et al, 04; Hinek et al, 2005; Alexander et al ., 2005; White et al ., 2005. 2 Lin et al ., 2008 represented the compilation of Gripp et al ., 2006 and Estep et al, 2006; Kerr et al ., 2006; Steens et al, 2006; Zampino et al, 2006; Digilio et al ., 2007; Limongelli et al ., 2007; Denayer et al ., 2007; Lo et al ., 2008; Hou et al ., 2008; Gripp et al, 2008. 3 Case reports in the literature who were later included in extensive reviews were generally reported only in Group II, e.g. patients 1 and 3 in Zampino et al , 1993 were also patients CS-01 and CS-04 in Zampino et al, 2006).…”
Section: Figurementioning
confidence: 99%
“…GH deficiency, adrenal insufficiency, hyperinsulinemic hypoglycemia, parathyroid adenoma with hyperprolactinemia and hypoglycemia [Johnson et al, 1998;Gregersen and Viljoen, 2004;Stein et al, 2004;Alexander et al, 2005;White et al, 2005] have all been reported in CS patients. The administration of rhGH in CS individuals with GH deficiency has been successful without adverse events till now [Gripp et al, 2000;Gregersen and Viljoen, 2004;Stein et al, 2004;White et al, 2005] despite concerns about the potential impact on cardiomyopathy progression and tumor risk [Kerr et al, 2003]. Osteoporosis, central hypogonadism and delayed puberty are not rare in the young adult [White et al, 2005].…”
mentioning
confidence: 95%